A comparative study: Effects of different nanoparticles on the properties of gold mine tailings containing cement mortars - Ozen, Meral Yildirim; Derun, Emek Moroydor (ELSEVIER SCI LTD, 2019)
In this study, fresh and hardened features of gold mine tailings containing cement mortars prepared with various ratios of CuO, SiO2, and Al2O3 nanoparticles were investigated. The setting time, compressive and flexural strength, Differential thermal analysis (DTA)/Thermogravimetric analysis (TG), Brunauer-Emm ett-Teller (BET), X-ray diffraction (XRD), Fourier Transformed Infra-Red (FT-IR), Scanning Electron Microscope (SEM) and water absorption tests were carried out to observe the mechanical, thermal and durability properties of mortars. According to analyses results, the highest increment in the compressive strength was obtained for 0.2 wt% Sio(2) addition as 11.46%. BET results conformed to strength test results and lower ratios of nano-CuO and nano-SiO2 improved the microstructure of mortars when nano-Al2O3 did not show the same effects for all replacement ratios. On the other hand, 2.5 wt% nano-Al2O3 increased the water absorption resistance of mortar up to 45.22% of the reference sample. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: Cement mortar; Gold mine tailings; Mechanical properties; Microstructure; Nanoparticle; Water absorption; SELF-COMPACTING CONCRETE; HIGH-STRENGTH MORTARS; CUO NANOPARTICLES; FLY-ASH; MICROSTRUCTURAL PROPERTIES; MECHANICAL-PROPERTIES; NANO-ALUMINA; RAW MIX; NANO-SIO2; HYDRATION; Construction & Building Technology; Engineering; Materials Science